Transient Congenital Complete Heart Block: A Case Report - Ying-Tzu Ju; Yu-Jen Wei; Ming-Ling Hsieh; Jieh-Neng Wang; Jing-Ming Wu (MDPI AG, 2021)
Congenital complete heart block is defined as a complete atrioventricular block occurring prenatally, at birth, or within the first month of life. Congenital complete heart block has a high mortality rate, and in infants with normal heart morphology, it is often associated with maternal connective tissue disease. In these latter cases, neonatal congenital complete heart block is usually irreversible. We present a rare case of a female neonate who had bradycardia noted at a gestational age of 37 weeks. Her mother had no autoimmune disease history. She had no structural heart disease, and the serology surveys for autoantibodies including SSA/Ro and SSB/La were all negative. Without intervention or medication, her congenital complete heart block completely recovered to a normal sinus rhythm within 5 days. The cause of the transient congenital complete heart block was unknown in this case.